2021
DOI: 10.1155/2021/2298973
|View full text |Cite
|
Sign up to set email alerts
|

A Hypoxia Signature for Predicting Prognosis and Tumor Immune Microenvironment in Adrenocortical Carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy with dismal prognosis. Hypoxia is one of characteristics of cancer leading to tumor progression. For ACC, however, no reliable prognostic signature on the basis of hypoxia genes has been built. Our study aimed to develop a hypoxia-associated gene signature in ACC. Data of ACC patients were obtained from TCGA and GEO databases. The genes included in hypoxia risk signature were identified using the Cox regression analysis as well as LASSO regression analysis. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Zhou et al found that CCNA2 is a potential diagnostic and prognostic biomarker for LUAD, and CCNA2 expression positively correlated with immunity therapy efficiency in LUAD [42]. Chen et al also confirmed that CCNA2 is involved in hypoxia signature affecting the clinical outcomes and immune microenvironment of ACC [43]. To date, only several studies assessed the immune role of CCNA2 in cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Zhou et al found that CCNA2 is a potential diagnostic and prognostic biomarker for LUAD, and CCNA2 expression positively correlated with immunity therapy efficiency in LUAD [42]. Chen et al also confirmed that CCNA2 is involved in hypoxia signature affecting the clinical outcomes and immune microenvironment of ACC [43]. To date, only several studies assessed the immune role of CCNA2 in cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, autophagy might act as a survival mechanism for tumor hypoxic cells through recycling of cellular constituents. The hypoxia risk signature was recently suggested to be able to predict prognosis and evaluate the tumor immune microenvironment of ACC (82) and also the long common history between hypoxia and PCC (83), indicate to us that in adrenal tumorsit would be interesting to study the hypoxia status and relate it with improved therapeutic strategies using autophagy modulation.…”
Section: Final Remarksmentioning
confidence: 99%
“…Tumor associated hypoxia could be one of the players of erythropoietin production in tumor cells. Recently, a bioinformatic study has reported that a hypoxia-related gene signature could predict prognosis and reflect the immune microenvironment in ACC ( 126 ). Specifically, based on hypoxia-related gene expression, ACC patients in the TCGA database were divided into three molecular subtypes (C1, C2, and C3), each with different clinical outcomes with C3 having reported of shortest survival ( 127 ).…”
Section: Hypoxia Inducible Factors: Overview Of Structure Function An...mentioning
confidence: 99%